How to Evaluate BDD Scenarios' Quality? - Oliveira, Gabriel; Marczak, Sabrina; Moralles, Cassiano (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
A scenario from the Behavior-driven development (BDD) practice is a known format to represent acceptance tests in agile methodologies, communicating assumptions and expectations by expressing the details that result from the conversations between customers and developers. We believe that this formalization of behavior need to be of good quality to avoid known requirement problems that arise from bad documentation, such as incomplete, underspecified and inconsistent requirements. However, there are only informal guidelines to guide practitioners on their BDD scenarios' elaboration and quality evaluations. To address this lack of guidance, we define a set of quality attributes and propose a question-based checklist to assist BDD scenarios' quality evaluations. [Methods] The quality attributes were identified from an interview-based study with 18 practitioners. In this study, practitioners shared their interpretations on an initial set of literature-informed quality attributes and their own personal evaluation criteria. We consolidated both in a single list of newly redefined attributes, used in the definition of our proposed checklist. We believe that our newly re-defined quality attributes and question-based checklist can enhance the existing guidelines and practitioners' ability to evaluate BDD scenario's quality by providing them with an standard guideline for scenarios' refinement conversations.